Survey of the teaching methods of human computer interaction - Lapin, Kristina (Lietuvos matematikos rinkinys, 2004)
The paper surveys teaching methods of both sciences and engineering that are implemented in the Human Computer Interaction courses. It deals with traditional lecture-based, case-based and pattern-based teaching.
Keywords: teaching methodology; HCI